ENTREPRENEURIAL BEHAVIOUR OF RURAL WOMEN INVOLVED IN HANDLOOM INDUSTRY OF ASSAM - DEEKSHITA DUTTA*; T. RADHA (The Journal of Research ANGRAU, 2022)
This study was conducted in the Lakhimpur district of Assam in August, 2021 with an objective to analyse the entrepreneurial behaviour of rural women involved in handloom industry. The researcher selected 25 women from two villages using random sampling method, thus, making a total sample size of 50 respondents. The nine dimensions of entrepreneurial behaviour were studied to evaluate the level of entrepreneurial behaviour i.e. innovativeness, achievement motivation, decision-making ability, risk-orientation, information-seeking behaviour, cosmopoliteness, self-confidence, economic motivation and management orientation. The results revealed that more than half of the respondents (56%) had medium level of entrepreneurial behaviour, followed by respondents with low level of entrepreneurial behaviour comprising of 28%. Only 16% of the respondents were found to have high level of entrepreneurial behaviour.